A discrete formulation of Kirchhoff rods in large-motion dynamics. (May 2020) - Giorgio, Ivan
A nonlinear model for the dynamics of a Kirchhoff rod in the three-dimensional space is developed in the framework of a discrete elastic theory. The formulation avoids the use of Euler angles for the orientation of the rod cross-sections to provide a computationally singularity-free parameterization of rotations along the motion trajectories. The material directions related to the principal axes of the cross-sections are specified using auxiliary points that must satisfy constraints enforced by the Lagrange multipliers method. A generalization of this approach is presented to take into account Poisson's effect in an orthotropic rod. Numerical simulations are performed to test the presented formulation.